Study of Various Key Process Parameters of FDM 3D Printed Parts using Ultimaker 2+ 3D Printer - Soham Kulkarni,; Praharsh Sah,; Ninad Kulkarni,; Prof. Vaibhav Kulkarni, (International Journal of Engineering and Management Research, 2023)
This research paper aims to investigate the effect of different Fused Deposition Modelling (FDM) printing parameters on the mechanical properties of printed parts. FDM is one of the most widely used 3D printing technologies due to its versatility and low cost. However, the mechanical properties of FDM printed parts depend largely on the printing parameters used. A series of tensile tests were conducted on FDM printed parts with varying printing parameters such as layer height, infill density, print speed, and nozzle temperature. The results showed that increasing the layer height and infill density improved the mechanical properties of the printed parts, while increasing the print speed decreased the mechanical properties. Nozzle temperature also had a significant effect on the mechanical properties of the printed parts, with a higher temperature resulting in stronger parts. Overall, this research provides valuable insights into the effects of different FDM printing parameters on the mechanical properties of printed parts and can be used to optimize FDM printing for specific applications. The research value of this case study is to obtain the best suitable key process parameters for FDM printing.